Pengaruh Harga, Lokasi Dan Kualitas Pelayanan Terhadap Loyalitas Konsumen Pada The Bake Corner Kediri - Elvina Poppy Sagita; Bambang Suwarsono; Brahma Wahyu Kurniawan (Intellektika : Jurnal Ilmiah Mahasiswa, 2023)
Repurchase of a product by consumers is a manifestation of the formation of loyalty in consumers. Consumer loyalty can be formed because it is influenced by several factors. Several factors that are believed to influence consumer loyalty are product price, purchase location, and service quality. So this research aims to determine the influence of price, location and service quality on consumer loyalty at The Bake Corner Kediri, both partially and simultaneously. This research is quantitative research carried out at The Bake Corner Kediri, Kediri City, East Java. The research population was taken from consumers in the last 3 months with a total of 1,080 people. Meanwhile, the sample used was 92 people, determined using the Slovin formula calculation. The data used is primary data taken using observation techniques and closed interviews using questionnaires. The data was then analyzed using multiple linear regression tests using SPSS. Based on the analysis results, it is known that price, location and service quality have a positive and significant effect on consumer loyalty. Simultaneously, price, location and service quality also have a significant influence on consumer loyalty at The Bake Corner Kediri. It is hoped that The Bake Corner Kediri will further develop several factors that can influence consumer loyalty.